Outcome of Endoscopic Endonasal Repair of CSF Rhinorhea using Fascia Lata Graft - Hani Musa Al-Akbi1, Ahmed Adhab Mayan2, Ammar Jabbar Najm Alkelabi3, Laith Ali Mahmood4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Cerebrospinal fluid rhinorrhea occur when there is communication between skull base and the nasal cavity. Nowadays endoscopic endonasal repair of CSF rhinorrhea become the preferred surgical intervention.Setting:ENT department at Ghazi AL Hariri Hospital for specialised surgeries, Medical City, Baghdad, Iraq.Aim: To assess the effectiveness of fascia lata as sealing graft in the endoscopic endonasal repair of CSF rhinorrhea.Patients and Method: Fifteen patients present to our department with possible clinical diagnosis of CSF rhinorrhea. The patients submitted to full history, examination including nasal endoscopy, radiological investigation (CT and MRI) of the nose and paranasal sinuses and skull base and CSF analysis. Operative technique was endoscopic endonasal repair using fascia lata graft .With monthly follow-up.Results: Successful rate noted in 93% of the patients .No recurrence of meningitis attacks among those who reported meningitis on their presenting illness.Conclusion: Endoscopic endonasal repair of CSF rhinorrhea has less operative and postoperative complication. Fascia lata graft offers a good choice for the repair.